Investigation of Natural Product Extracts as Green Corrosion Inhibitors on Steels and Alloys: Experimental and Theoretical Approach - Muhamad Akrom; Wahyu Aji Eko Prabowo (Prosiding ESEC, 2022)
Natural plant extracts show excellent performance as green corrosion inhibitors on steel with high inhibition efficiency. Experimental and theoretical methods are able to synergize in investigating corrosion inhibition performance. This report is a comparative literature for the development of natural-based inhibitors. The development of future investigations is expected to show the interaction of plant extract molecules with metal surfaces at the atomic level, so that a systematic and detailed understanding of the mechanism of corrosion inhibition in metal is obtained.